Clever Enough to Tell the Truth - Bradley Ruffle; Yossi Tobol (Institute for the Study of Labor (IZA), 2016)
We conduct a field experiment on 427 Israeli soldiers who each rolled a six-sided die in private and reported the outcome. For every point reported, the soldier received an additional half-hour early release from the army base on Thursday afternoon. We find that the higher a soldier's military entrance score, the more honest he is on average. We replicate this finding on a sample of 156 civilians paid in cash for their die reports. Furthermore, the civilian experiments reveal that two measures of cognitive ability predict honesty, whereas general self-report honesty questions and a consistency check among them are of no value. We provide a rationale for the relationship between cognitive ability and honesty and discuss its generalizability.
Keywords: C93; M51; 330; soldiers; cognitive ability; honesty; high non-monetary stakes